Polar Bear Studies During 1966 - Flyger, Vagn (ARCTIC, 1967)
Polar bear migratory habits and population dynamics are relatively unknown and to learn more about these aspects, the Arctic Institute of North America (AINA) is supporting a long-range, research project. With funds from the Office of Naval Research the Institute sent Dr. Martin W. Schein to the Arctic Research Laboratory at Point Barrow during April 1965 and he returned to ARL with Dr. Vagn Flyger in March 1966. With the help of the able pilots at the Arctic Research Laboratory and their small ski equipped airplanes, they developed the following technique for capturing bears. When weather permitted they flew out over the ice in the general area north of Point Barrow with Cessna 180 airplanes. While one airplane flew at an elevation of about 100 feet and searched for polar bear tracks, the other airplane, containing Flyger and Schein, flew slightly behind and at an altitude of about 500 feet. Upon finding polar bear tracks, the planes followed them until they came upon the bear. The plane containing the biologists went on ahead about two or three miles in the direction the bear was travelling and deposited Flyger and Schein on the ice where they hid behind a pressure ridge. The plane then took off and the two planes drove the bear to the waiting biologists. When the bear got to within approximately 50 yards, it was shot with an automatic projectile syringe from a rifle. Syringes contained the drug succinylcholine chloride which paralyzed the bear within a few minutes. While the bears were immobile, they were examined, measured, and marked with ear tags and dye so that they could be recognized later if seen. Five bears were captured but of these four died because of a combination of overdoses of the drug and circumstances connected with chasing the bear with aircraft. Much, however, was learned from these animals which made it possible to be more successful in capturing and marking bears in Svalbard during August 1966. The Norsk Polarinstitutt invited Dr. Flyger, supported by AINA, and Dr. Albert W. Erickson, ...